2016
DOI: 10.1080/23279095.2016.1248765
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of acute head injury in an emergency department population using sport concussion assessment tool – 3rd edition

Abstract: Sport Concussion Assessment Tool version 3 (SCAT-3) is one of the most widely researched concussion assessment tools in athletes. Here normative data for SCAT3 in nonathletes are presented. The SCAT3 was administered to 98 nonathlete healthy controls, as well as 118 participants with head-injury and 46 participants with other body trauma (OI) presenting to the ED. Reference values were derived and classifier functions were built to assess the accuracy of SCAT3. The control population had a mean of 2.30 (SD = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 23 publications
2
32
1
Order By: Relevance
“…8,26 The observed shift in type of healthcare provider encountered, specifically the decrease in claims for care by ambulance and radiology providers, can be partly attributed to the increased treatment of mild injuries at ED and/or the reduced reliance on imaging, which is needed only if a more severe TBI is suspected. Previous studies have demonstrated the Sport Concussion Assessment Tool-3rd edition (SCAT3) and ChildSCAT3 for children ages 5-12 years had a high sensitivity in measuring the signs and symptoms of concussions in an ED setting, 27,28 reducing the need for diagnostic radiology. Moreover, the Pediatric Emergency Care Applied Research Network has advised against the use of imaging in children without severe signs and symptoms, further decreasing the number of healthcare encounters in radiology post-law.…”
Section: Discussionmentioning
confidence: 99%
“…8,26 The observed shift in type of healthcare provider encountered, specifically the decrease in claims for care by ambulance and radiology providers, can be partly attributed to the increased treatment of mild injuries at ED and/or the reduced reliance on imaging, which is needed only if a more severe TBI is suspected. Previous studies have demonstrated the Sport Concussion Assessment Tool-3rd edition (SCAT3) and ChildSCAT3 for children ages 5-12 years had a high sensitivity in measuring the signs and symptoms of concussions in an ED setting, 27,28 reducing the need for diagnostic radiology. Moreover, the Pediatric Emergency Care Applied Research Network has advised against the use of imaging in children without severe signs and symptoms, further decreasing the number of healthcare encounters in radiology post-law.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 9 17 The CSSS has also been used to monitor recovery after injury 7 , 9 , 18 and in non-sport-related TBI patients with injuries severe enough to require computed tomography (CT) imaging. 19 …”
Section: Introductionmentioning
confidence: 99%
“…The average number of SCAT3 symptoms endorsed has been estimated between 1.75 and 3.2 for the general population. [15][16][17] By comparison, the number of these symptoms endorsed by youth athletes who sustained HIs was 9.7. 16 Consistent with these studies, our data revealed a higher number of postconcussive symptoms endorsed by cyclists who reported HIs versus those who did not.…”
Section: Discussionmentioning
confidence: 95%